Kohl, Reagan, and Open Economy Macroeconomics: Revisiting Rules for Fiscal and Monetary Policy. - Tirelli, P; Vines, D (1995)
This paper models three alternative policy strategies for an open economy and evaluates their performance. In the first regime national monetary policies are used to achieve domestic price stability, without supporting fiscal policy and without concern for external balance. The second regime adds to this fiscal policy assigned to controlling the external balance. In the third regime, monetary policy, via the exchange rate, is assigned to external balance and fiscal policy is used to control inflation. We show that the first regime might be unstable, or, if stable, that it might give rise to large swings in foreign wealth holdings and in real exchange rates. These problems can be avoided in either of the other two regimes, but the fluctuations in the real interest rate and the real exchange rate in response to shocks are larger in the second regime than in the third.